INFECÇÃO PELO HIV: PREVALÊNCIA, PrEP E A TECNOLOGIA A FAVOR DE ESTRATÉGIAS DE PREVENÇÃO - Gabriela Alves Cesar (2022)
The fight against the epidemic caused by the human immunodeficiency virus (HIV) infection is continuous and timeless. This infection has lasted for more than 40 years and has a high incidence rate. In Brazil, the epidemic is concentrated in some population groups that are at increased risk of acquiring HIV infection. Based on this information, the Ministry of Health started to make available strategies aimed at the prevention of HIV infection, called Combined Prevention, and among them is oral Pre-Exposure Prophylaxis (PrEP). PrEP consists of the use of daily antiretroviral drugs that prevent HIV infection even in cases of exposure to this virus. Therefore, the first study aimed to study the epidemiological and molecular aspects of HIV infection in men who have sex with men (MSM), transgender women, and transvestites (TW) in order to minimize gaps in the prevention of HIV infection. In the second study, the objective was to evaluate the sociodemographic data and the incidence rate of sexually transmitted infections (STI) in the PrEP user population seen at the Center for Testing and Counseling (CTA) in Campo Grande, Mato Grosso do Sul. To achieve the objectives of the third study, software was developed with warnings and information aimed at improving the quality of life, adherence, and rational use of PrEP. The first study was conducted with 430 participants, 278, MSM and 152 TW. The prevalence of HIV infection in this population was 9% (25/278) among MSM and 24.3% (37/152) among TW, prevalences similar to those found in other Brazilian cities. After uni and multivariate analysis, the variable age greater than or equal to 30 years was associated with HIV infection in MSM. While for the TW group, the associated variables were: having been forced to have sex with someone, HIV and syphilis co-infection, HIV and hepatitis C (HCV) co-infection. Regarding phylogenetic analyses, 65% of the sequences were classified as subtype B. In the second study, 261 PrEP users were included, most of thageswith age ranging from 18 to 30 years. Among them, 92.7% (241/261) were biologically male. Regarding gender identity, 84.6% were gay or MSM while 7.6% were transgender women and 7.6% were cisgender women. 31/261 new syphilis cases were identified with an incidence rate of 11.8 per 100 persons/year, 7/261 new HIV cases and 3/261 new HIV and syphilis coinfection cases were identified in the study population. After univariate and multivariate analysis, the history of sexual contact with a person of the same sex remained associated with new cases of STIs. Regarding the software development, the National Institute of Industrial Property issued the software registration certificates BR 51202101589-4; BR 5120211590-8, and BR 512021001591-6. The results show a high prevalence of HIV infection in MSM and TW when compared to rates observed in the general population. Most PrEP users are young and MSM, highlighting the urgent need for specific public health policies that increase the participation of women and transgender people regarding diagnosis, treatment and prevention measures. The development of new technologies can contribute to the monitoring, adherence and rational use of PrEP, thus aiming at reducing new cases of HIV infection. Keywords: HIV, Combination Prevention, Pre-Exposure Prophylaxis (PrEP).